2020
DOI: 10.1039/d0qi00860e
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the inhibition of enzymes by polyoxometalates

Abstract: Polyoxometalate (POMs) is a kind of inorganic cluster metal complexes with various biological activities, such as anti-Alzheimer's disease, antibacterial, anti-cancer, anti-diabetes, anti-virus and so on. The mechanism of their action...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 63 publications
0
17
0
1
Order By: Relevance
“…For instance, Lampl et al demonstrated that Wells-Dawson polyoxometalates could serve as tyrosinase inhibitors and significantly slow down the browning of mushroom [ 21 ]. Similarly, Hu et al also synthesized a Wells-Dawson phosphotungstic polyoxometalate and confirmed its inhibitory effects on mushroom tyrosinase [ 22 ]. Recent research also showed the polyoxometalates could be used to prevent browning of apple slices [ 23 ] and lotus root slices [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lampl et al demonstrated that Wells-Dawson polyoxometalates could serve as tyrosinase inhibitors and significantly slow down the browning of mushroom [ 21 ]. Similarly, Hu et al also synthesized a Wells-Dawson phosphotungstic polyoxometalate and confirmed its inhibitory effects on mushroom tyrosinase [ 22 ]. Recent research also showed the polyoxometalates could be used to prevent browning of apple slices [ 23 ] and lotus root slices [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 Despite such indications, the redox activity of Ce IV -POMs towards proteins, and the interplay between redox and hydrolytic reactions have not been addressed in detail. Although interactions between POMs and proteins have been well studied on a molecular level, 18,[25][26][27] the redox chemistry between inorganic clusters and proteins is a virtually unexplored eld. Therefore, we set out to investigate the redox reactivity of a Ce IV -POM towards a protein substrate and evaluate how such reactivity impacts the hydrolytic reaction that leads to protein fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…75 © 2021 The Author(s 85 POMs can bind to and inhibit a large number of proteins and enzymes in vitro, such as a cationic pocket in HIV-1 protease, 87 but such targets are yet to be veried in vivo. 88 POMs exhibit promising antibacterial activity. 89 An early report of antibacterial activity suggested synergism with conventional antibiotics.…”
Section: Antiviral and Antibacterial Polyoxometallatesmentioning
confidence: 99%
“… 85 POMs can bind to and inhibit a large number of proteins and enzymes in vitro , such as a cationic pocket in HIV-1 protease, 87 but such targets are yet to be verified in vivo . 88 …”
Section: Viruses and Microbesmentioning
confidence: 99%